Synchronous Resection of Solitary Liver Metastases with Pancreaticoduodenectomy - Singh, Amanjeet; Singh, Tanveer; Chaudhary, Adarsh (JOP. Journal of the Pancreas, 2010)
Context There is limited information available about the feasibility and benefits of synchronous resection of liver metastases in patients with pancreatic and periampullary cancer undergoing pancreaticoduodenectomy. Objective We report on our experience with 7 such patients. Design Analysis of the prospective database was carried out to identify patients who underwent synchronous resection of liver metastases with pancreaticoduodenectomy. Patients Two-hundred and thirty patients underwent pancreaticoduodenectomy for pancreatic and periampullary cancer in our unit between September 2003 and September 2009. Main outcome measures The primary aim of our study was to determine the survival benefits and the secondary aim was to evaluate their safety and influence on the results of a pancreaticoduodenectomy. Results Seven patients (3%) underwent synchronous resection of a solitary liver metastasis. In these patients, the operative time and intra-operative blood loss was marginally high as compared to the overall cohort of patients undergoing pancreaticoduodenectomy; however, the complication rates and the duration of the hospital stay were not affected. In patients undergoing resection of liver metastasis, there were 4 recurrences over a mean follow-up of 21 months. Conclusions In patients with resectable pancreatic and periampullary cancer, the resection of a solitary liver metastasis can safely be performed together with a pancreaticoduodenectomy; however, its impact on improving survival has yet to be proven. Image: Sir Ganga Ram Hospital, Rajinder Nagar. New Delhi, India.